Some New Discrete Gronwall-Bellman Type Inequalities with Three Independent Variables and Applications. (1st August 2018) - Liu, Weihua; Huang, Haisong
Abstract : Some new discrete Gronwall-Bellman type inequalities with three independent variables which generalize some existing results and can be used as handy tools in the study of qualitative and quantitative properties of solutions of certain classes of difference equation are presented. As applications, some difference equations with the initial boundary conditions are also considered.